I Cannot Tell a Lie: The Standard for New Trial in False Testimony Cases - Wolf, Daniel (1985)
This Note examines the question of what standard should be used for granting a new trial when a defendant's conviction is alleged to have been based, at least in part, on false testimony. Part I demonstrates the failure of the existing standards to strike a satisfactory balance between defendants' rights and the efficient administration of the criminal justice system. Part II argues that motions for retrial based upon false testimony should be governed by a standard drawn not only from newly discovered evidence cases generally, but also from cases involving prosecutorial misconduct. Finally, Part III suggests that the proper test for new trial based upon newly discovered evidence of false testimony is whether there is a significant chance that a jury with knowledge of false testimony would avoid conviction. This test both guards against convictions based upon false testimony and preserves the finality of judgments necessary for the sound and efficient administration of criminal justice. A proper balance between these often competing goals will enhance the interests of justice that rule 33 is designed to protect